Domain-specific cognitive impairment in patients with COPD and control subjects - Cleutjens, Fiona AHM; Franssen, Frits ME; Spruit, Martijn A; Vanfleteren, Lowie EGW; Gijsen, Candy; Dijkstra, Jeanette B; Ponds, Rudolf WHM; Wouters, Emiel FM; Janssen, Daisy JA (International journal of chronic obstructive pulmonary disease, 2017)
Impaired cognitive function is increasingly recognized in COPD. Yet, the prevalence of cognitive impairment in specific cognitive domains in COPD has been poorly studied. The aim of this cross-sectional observational study was to compare the prevalence of domain-specific cognitive impairment between patients with COPD and non-COPD controls. A neuropsychological assessment was administered in 90 stable COPD patients and 90 non-COPD controls with comparable smoking status, age, and level of education. Six core tests from the Maastricht Aging Study were used to assess general cognitive impairment. By using -scores, compound scores were constructed for the following domains: psychomotor speed, planning, working memory, verbal memory, and cognitive flexibility. General cognitive impairment and domain-specific cognitive impairment were compared between COPD patients and controls after correction for comorbidities using multivariate linear and logistic regression models. General cognitive impairment was found in 56.7% of patients with COPD and in 13.3% of controls. Deficits in the following domains were more often present in patients with COPD after correction for comorbidities: psychomotor speed (17.8% vs 3.3%; <0.001), planning (17.8% vs 1.1%; <0.001), and cognitive flexibility (43.3% vs 12.2%; <0.001). General cognitive impairment and impairments in the domains psychomotor speed, planning, and cognitive flexibility affect the COPD patients more than their matched controls.